Effects of a sport specific training program targeting the pelvis, spine and trunk on throwing velocity and muscular power and endurance measures in college throwing athletes - Palmer T. G.; Mattacola, C. G.; Uhl, T. L.; Hewett, T. E.; Howell, D.; Viele, K. (Journal of Athletic Training, 2013)
The ability to stabilize and actively control the pelvis, spine and trunk, has been reported to influence sport performance yet there is limited evidence supporting that improvements in sport result from changes in the muscles supporting the pelvis, spine and trunk. Traditional interventions lack sport specific methods which target both the muscular power and endurance capabilities of the pelvis, spine, and trunk. Objective: To investigate the effect a traditional endurance training program and a sport specific power training program have on throwing velocity, muscular endurance and power measures of the proximal segments. We hypothesized there would be a significant difference (p d•.05) in change scores for throwing velocity, muscular power and muscular endurance between groups. Design: A randomized clinical trial with blocked stratification for sex and position was implemented with a pre- to postintervention design. Setting: Field and research laboratory. Patients or Other Participants: Forty-six healthy (mean age = 20 ± 1.3 years, height = 175.7 ± 8.7 cm, weight = 79 ± 13.9 Kg), Division III collegiate female softball (n=17) and male baseball (n=29) players from the same institution volunteered and were randomly assigned to one of two training groups for 7 weeks; a traditional endurance training group (ET) (n=21) or a power training group (PT) (n=25). Interventions: The ET group performed a traditional endurance progression relative to the number of repetitions and time incorporating static and linear exercise movements of the pelvis, spine and trunk. The PT group received undulating blocked periodization consisting of endurance, strength and power movements specific to throwing. Main Outcome Measures: Peak throwing velocity (km/h) normalized for body weight (kg), muscular endurance prone plank tests (seconds) and power output from a one-repetition maximum chop test (watts/Kg body weight) were measured pre- and post- intervention. Student`s independent t-tests were used to compare differences between the change score for all dependent variables with alpha level set at pd".05. Results: The peak throwing velocity change score was significantly faster by 6±2% in the PT group (ET= .01±.1 km/h/kg of body weight, PT= .08±.03 km/h/kg of body weight, p< .001) at post-intervention compared to the ET group. Muscular endurance was not different between groups (ET= 154 ±54, PT= 151±42, p= .901). The power chop test improved in PT group (105 ±68 watts) compared to the ET group (20 ±78 watts) (p<.001) CONCLUSION: This is the first study to demonstrate improvements in muscle performance for the proximal segments simultaneously with a sport performance measure in throwing velocity. Sport specific training that targets the pelvis, spine and trunk is beneficial to muscular power measures and throwing performance.